Dental health status of skeletal remains excavated from an abandoned well at Ajnala, India: a bioarchaeological study - Sehrawat, Jagmahender Singh; Singh, Monika (Anthropological Review, 2018)
Present study was conducted to assess dental health status of the mid-19th century skeletal remains excavated from an abandoned ancient well and to scrutinize the demographic affiliations of the remains. Thousands of bones, teeth and contextual items were excavated non-scientifically from an abandoned well situated underneath a religious structure at Ajnala (Amritsar, India). Four thousands four hundred and seventy five teeth of each type were examined for presence of dental pathologies of caries, wear and linear enamel hypoplasia (LEH). The frequency distribution of each pathological state was calculated for each tooth type using international dental standards available in the literature. The overall dental status was characteristic of young individuals having low prevalence of dental caries and enamel hypoplasiac lesions. Very few teeth had seriously exposed dentine and pulp cavity; indicating consumption of some cariogenic food items. The maxillary and posterior teeth were more affected with dental caries than the mandibular and anterior teeth. LEH defects were found more commonly distributed in the lower canines (44.9%) and upper incisors (34.8%) than their corresponding counterparts and statistically significant differences were noticed in LEH prevalence between anterior and, posterior dentition. The overall percentage of LEH has been found as 15.8%; with 15.4% maxillary and 16.2% mandibular teeth being affected with LEH. The paleodontogical examinations, contextual items and the preliminary molecular findings supported the written versions that victims of Ajnala skeletal remains had sound dental health status and probably belonged to adult males who were killed in 1857 as per written versions.